Ranolazine preserves and improves left ventricular ejection fraction and autonomic measures when added to guideline-driven therapy in chronic heart failure - Murray, Gary L. (Heart Int, 2014)
BACKGROUND: Ranolazine (RAN) reduces cardiac sodium channel 1.5’s late sodium current in congestive heart failure (CHF), reducing myocardial calcium overload, potentially improving left ventricular (LV) function. RAN blocks neuronal sodium channel 1.7, potentially altering parasympathetic and sympathetic (P&S) activity. The effects of RAN on LV ejection fraction (LVEF) and P&S function in CHF were studied. METHODS: Matched CHF patients were given open-label RAN (1000 mg po-bid) added to guideline-driven therapy (RANCHF, 41 systolic, 13 diastolic) or no adjuvant therapy (control, NORANCHF, 43 systolic, 12 diastolic). Echocardiographic LVEF and P&S measures were obtained at baseline and follow-up (mean 23.7 months). RESULTS: LVEF increased in 70% of RANCHF patients, an average of 11.3 units. Mean LVEF remained unchanged in NORANCHF patients. P&S measures indicated cardiovascular autonomic neuropathy (P≤0.1 bpm(2)) in 20% of NORANCHF patients at baseline and in 29% at follow-up (increasing in both groups). At baseline, 28% of patients had high sympathovagal balance (SB), RAN normalized SB over 50% of these; in contrast, the NORANCHF group had a 20% increase in patients with high SB. CONCLUSIONS: RAN preserves or improves LVEF and decreases high SB in CHF.